An approach for unipolar corona discharge in N2/O2 gas mixture by considering townsend conditions - Alisoy, Hafiz Z.; Yesil, Ali; Koseoglu, Murat; Unal, Ibrahim (Elsevier Science Bv, 2011)
In this study (alpha/p)=f(E/p) functional relation is derived for the gas mixture of N-2/O-2 by considering Townsend approach, and formation mechanism of corona discharge is investigated for the coaxial electrode system located in this gas medium. The electron energy distribution function (EEDF) which is required for estimation of ionization coefficient, is determined by considering probability distribution function of inelastic electron collisions versus energy. An algorithm for determining ionization coefficient for binary gas mixture is presented. The development and motion of the electron avalanche in inter-electrode gap are studied by considering the effect of positive space charges. It is determined by considering the derived mathematical expressions that the formation of corona discharge is related with the variation of the current characteristics in inter-electrode gaps depending on the change of potential of central electrode. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Corona; Gas discharges; Ionization